2020
DOI: 10.1155/2020/4293071
|View full text |Cite
|
Sign up to set email alerts
|

What and How Can Physical Activity Prevention Function on Parkinson’s Disease?

Abstract: Aim. This study was aimed at investigating the effects and molecular mechanisms of physical activity intervention on Parkinson’s disease (PD) and providing theoretical guidance for the prevention and treatment of PD. Methods. Four electronic databases up to December 2019 were searched (PubMed, Springer, Elsevier, and Wiley database), 176 articles were selected. Literature data were analyzed by the logic analysis method. Results. (1) Risk factors of PD include dairy products, pesticides, traumatic brain injury,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 188 publications
(198 reference statements)
1
23
0
5
Order By: Relevance
“…Diet regulation and exercise not only reduce body weight but also affect synaptic plasticity and protect against cognitive and neurological diseases. Studies have shown that long-term participation in reasonable physical exercises, such as running, boxing, swimming and dancing, has a beneficial effect on the motor and nonmotor symptoms of PD patients, which greatly improves their quality of life [ 106 , 107 ]. Physical exercise also reduces the accumulation of α-Syn, inflammation and oxidative stress; increases the level of brain-derived neurotrophic factor (BDNF); and enhances the function of mitochondria to maintain cellular energy metabolism [ 107 ].…”
Section: Obesity Hypercholesterolemia and Pdmentioning
confidence: 99%
“…Diet regulation and exercise not only reduce body weight but also affect synaptic plasticity and protect against cognitive and neurological diseases. Studies have shown that long-term participation in reasonable physical exercises, such as running, boxing, swimming and dancing, has a beneficial effect on the motor and nonmotor symptoms of PD patients, which greatly improves their quality of life [ 106 , 107 ]. Physical exercise also reduces the accumulation of α-Syn, inflammation and oxidative stress; increases the level of brain-derived neurotrophic factor (BDNF); and enhances the function of mitochondria to maintain cellular energy metabolism [ 107 ].…”
Section: Obesity Hypercholesterolemia and Pdmentioning
confidence: 99%
“…This debilitating fear of movement can also be considered a factor that intensifies one’s limited activity levels. At all times, it is important to bear in mind that moderate physical activity has a positive impact on PD and should be used as a treatment to alleviate symptoms such as motor dysfunction, cognitive deficits, and depression [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, according to Fan et al [ 18 ], physical exercise, especially those performed at moderate to vigorous intensities, has a positive impact on PD through multiple mechanisms, including reduction of α-synuclein protein accumulation, decrease in inflammation and oxidative stress, improvement in brain-derived neurotrophic factor (BDNF) activity, nerve regeneration, and mitochondrial function. Furthermore, some authors have shown that endurance exercise is safe and well-tolerated for people with PD from a cardiovascular point of view, which supports their recommendation for this population [ 19 ].…”
Section: Introductionmentioning
confidence: 66%